Changes in Characteristics and Practice Patterns of Ontario Psychiatrists: Implications for Access to Psychiatrists. (January 2017) - Kurdyak, Paul; Zaheer, Juveria; Cheng, Joyce; Rudoler, David; Mulsant, Benoit H.
Objective: The objective of this study was to evaluate the changes in demographic, geographic, and practice characteristics of all Ontario psychiatrists between 2003 and 2013 and their implication for access to psychiatrists. Methods: We included all psychiatrists who were clinically active in Ontario in any year from 2003 to 2013. For each psychiatrist, we reported age, sex, years since medical school graduation, geographic practice region, and practice characteristics such as total number of inpatients, outpatients, and outpatient visit frequencies. Results: In 2013, there were 2070 psychiatrists, with nearly half (47%) more than 30 years since medical school graduation. Female psychiatrists comprised 41% of all psychiatrists in 2013 but 56% of all psychiatrists within 15 years of medical school graduation. Between 2003 and 2013, there was a 17% increase in the total number of psychiatrists, with the largest growth in psychiatrists occurring in the group more than 30 years from medical school graduation. Over these 11 years, the mean (SD) number of unique outpatients seen by a psychiatrist annually increased from 208 (228) to 249 (275) (19.5%; P = 0.001), with male psychiatrists, on average, seeing more outpatients annually than female psychiatrists. Conclusion: The number of outpatients seen by psychiatrists is slowly increasing. However, the large proportion of aging psychiatrists, the high concentration of psychiatrists in urban settings, and the increase in the number of female psychiatrists with smaller practices suggest that without radical changes to the way psychiatrists practice, access to psychiatrists will remain a challenge in Ontario.